Pemberdayaan Masyarakat Berbasis Masjid: Studi pada Masjid Besar Al Amin Sei Kera Hulu, Kec. Medan Perjuangan, Kota Medan, Sumatera Utara - Ajengesti Latifah Sabrinasyah; Dini Lestari Hasibuan; Rani Febrianti Siagianrani (Dakwatussifa: Journal of Da'wah and Communication, 2023)
The mosque has a very strategic function in Islamic society both as a place of worship and a media center for fostering people holistically. This paper describes the optimization of the function of the mosque as a center for community empowerment activities and the factors that influence it. The research method uses a qualitative descriptive method through interviews, field notes, and documentation. The place of research is the Great Mosque of Al Amin Medan. The results of the study show that the Great Mosque of Al Amin Medan represents a mosque capable of reviving the spirit of the community empowerment movement in the spiritual, economic, educational, social and cultural fields of development. The success of mosque-based community empowerment activities at the Great Al Amin Mosque is supported by adequate human resources which are reflected in the ideal organizational structure of the mosque's board of directors and are supported by the effective communication skills of the preachers. This study recommends the importance of professionalism in mosque management and the importance of managing effective communication with both the congregation and other stakeholders. This research enriches the study of Islamic community development, especially in empowering mosque-based communities. Keywords: Empowerment; Managmenet; Mosque